Tilan Island Tour in Rantau Bais Tourism Village: From Festival To Eco-tourism: Wisata Pulau Tilan di Desa Wisata Rantau Bais: Dari Festival Menuju Ekowisata - Candra Amrita, Devita; Hidir, Achmad; El Amady, M. Rawa (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
ABSTRACT:This study discussed about tourist destinations in Tilan Island, which was built under the initiative of the local youth through festival tourism. The tourist destination has been positively responded to by visitors whose number keeps increasing each year, and Kepenghuluan Rantau Bais has been recognised as a Tourism Village. Tourism in Tilan Island persistently transforms from festival tourism to regular tourism, starting from its opening every Saturday and Sunday. This study is a qualitative study that uses the ethnography method where the researcher lived for two months in Kepenghuluan Rantau Bais. The data was obtained using participative observation and in-depth interviews with an appointed informant who has a wide knowledge on tourism in Tilan Island. This research found that not all tourism potential in Tilan Island and Rokan River are explored to become tourist activities. ABSTRAK:Studi ini membahas tentang destinasi wisata Pulau Tilan, destinasi wisata yang dibangun atas inisiatif pemuda melalui wisata festival. Destinasi wisata sudah direspon positif oleh pengunjung yang datang terus meningkat setiap tahunnya, dan diakuinya Kepenghuluan Rantau Bais sebagai desa wisata. Wisata Pulau Tilan secara bertahap bertransformasi dari wisata festival ke wisata regular dimulai dengan dibukanya wisata pada setiap hari Sabtu dan Minggu. Studi ini merupakan studi kualitatif dengan menggunakan metode etnografi dimana peneliti tinggal selama dua bulan di Kepenghuluan Rantau Bais. Teknik pengambilan data melalui observasi partisipatif dan wawancara mendalam kepada informan yang ditetapkan karena pengetahuannya tentang wisata Pulau Tilan. Penelitian ini menemukan bahwa belum semua potensi wisata di Pulau Tilan dan Sungai Rokan dieksplorasi menjadi aktivitas wisata.